Penerapan Algoritma K-Means pada Ketersediaan Lapangan Olahraga Setiap Kelurahan Di Indonesia - Cristo Dhear Harafenta Lumbantobing; S Saifullah; Fitri Rizki (LPPM STIKOM Tunas Bangsa, 2020)
Sports facilities are the basis of sports activities such as athletic events such as volleyball, ball, tennis, and others. Each type of sports field requires advice and infrastructure to continue activities. The method used is Data Mining using the K-Means algorithm. This method of data is grouped into 2 clusters. The author uses data obtained from government sites that address http://bps.go.id. Based on recap result data from 2014 to 2018, The final results announced are based on sports fields, which are grouped into the lowest highest cluster based on the type of sport in each Kelurahan according to Indonesia's provinces. By using the K-Means method provides a grouping of an area in the Kelurahan, according to the Province in Indonesia. In this study, the government assisted in the sports field and improved facilities and infrastructure in sports for the athletic community.